DEVELOPMENT AND VALIDATION OF HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY WITH DIODE ARRAY DETECTOR METHOD TO ANALYSIS OF KAEMPFEROL MARKER FROM EXTRACTS OF POINCIANELLA PYRAMIDALIS (TUL) L.P QUEIROZ - Oliveira, Agna Helia de; Souza, Valmir Gomes de; Souza, FÃbio Santos de; Macedo, Rui Oliveira (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aims to develop the extraction of the marker kaempferol in the fluid extract (FE) and validate an analytical method that monitors the quality of extracts of P. pyramidalis. Methods: The P. pyramidalis leaves were collected and then were dried to milling process. The extracts were drawn up at 20% weight: Volume (w/v) by maceration, and the extraction system used was hydroethanol solution ratio at 50:50 volume: Volume (v: v). From the hydroalcoholic extract, a method of extracting the kaempferol biomarker was developed and validated by high-performance liquid chromatography coupled with diode array detector. To validate a method, the following parameters were evaluated: Specificity, selectivity, linearity, limit of quantification (LOQ) and detection (LOD), precision, accuracy, robustness, and stability. Results: The method developed proved to be efficient, as it allowed the analysis of the interferents free marker, with recovery above 90%, linear over the range 1.4–26.6 μg/mL, correlation coefficient R2=0.999, and LOD and LOQ 0.07 and 0.22 μg/mL, respectively, specificity, precision, accuracy, and robustness. Conclusion: The extraction methodology of the kaempferol marker was successfully developed interferents free and the validated method by HPLC-DAD represents a useful tool in the quality control of P. pyramidalis herbal medicines.